Structural requirement of the hydrophobic region of the Bordetella pertussis CyaA-hemolysin for functional association with CyaC-acyltransferase in toxin acylation - Veerada Raksanoh (2018)
© 2018 Elsevier Inc. Previously, we demonstrated that the ∼130-kDa CyaA-hemolysin (CyaA-Hly, Met482-Arg1706) from Bordetella pertussis was palmitoylated at Lys983when co-expressed with CyaC-acyltransferase in Escherichia coli, and thus activated its hemolytic activity. Here, further investigation on a possible requirement of the N-terminal hydrophobic region (HP, Met482-Leu750) for toxin acylation was performed. The ∼100-kDa RTX (Repeat-in-ToXin) fragment (CyaA-RTX, Ala751-Arg1706) containing the Lys983-acylation region (AR, Ala751-Gln1000), but lacking HP, was co-produced with CyaC in E. coli. Hemolysis assay indicated that CyaA-RTX showed no hemolytic activity. Additionally, MALDI-TOF/MS and LC-MS/MS analyses confirmed that CyaA-RTX was non-acylated, although the co-expressed CyaC-acyltransferase was able to hydrolyze its chromogenic substrate−p-nitrophenyl palmitate and acylate CyaA-Hly to become hemolytically active. Unlike CyaA-RTX, the ∼70-kDa His-tagged CyaA-HP/BI fragment which is hemolytically inactive and contains both HP and AR was constantly co-eluted with CyaC during IMAC-purification as the presence of CyaC was verified by Western blotting. Such potential interactions between the two proteins were also revealed by semi-native PAGE. Moreover, structural analysis via electrostatic potential calculations and molecular docking suggested that CyaA-HP comprising α1-α5 (Leu500-Val698) can interact with CyaC through several hydrogen and ionic bonds formed between their opposite electrostatic surfaces. Overall, our results demonstrated that the HP region of CyaA-Hly is conceivably required for not only membrane-pore formation but also functional association with CyaC-acyltransferase, and hence effective palmitoylation at Lys983.